Human capital, intrinsic motivation and poverty of elderly in later life - Mat Salleh, Supian; Halid, Noreha (Universiti Kebangsaan Malaysia, 2018)
This research analyzes the linkage between elderly poverty and children’s human capital level via income distribution, in which fertility decisions are motivated by old-age support with the assumption that the parents are non-altruistic. The paper provides a mathematical model looking at the relationship of old age poverty and the children human capital level with intrinsic motivation. Under the assumption that the parents depend solely on the children as the source of income in old age, the paper applies the overlapping generation model by incorporating intrinsic motivation. This study shows that, in the absence of public education, parents who choose not to invest in the private education of their children will be locked in a poverty trap. However, children with higher motivation show an improvement in their human capital evolution, and, thus, help the parents escape the poverty trap regardless of the parental economic status.